Spring Bed Business as a Livelihood for the People of Sei Semayang Village, Sunggal District, Deli Serdang Regency - Sitohang, Clara Angelina; Rumapea, Murni Eva Marlina (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The research aims to describe the reasons why the people of Sei Semayang Village chose the spring bed business as a livelihood, as well as outlining strategies for running a spring bed business as a livelihood. Qualitative research method with a descriptive approach, data collection techniques used in the research are interviews, observation, documentation carried out to add relevant data. The research method used from the research results is as follows: 1. Gaining knowledge from experience while working as an employee in a spring bed business owned by another entrepreneur is the reason people choose business as a livelihood. Fulfilling economic needs by choosing the spring bed business as a livelihood for people affected by the Covid-19 pandemic. Obtaining large profits is the reason why people run the spring bed business as a livelihood. The ease of making and obtaining raw materials by the community is the reason for choosing the spring bed business as a livelihood. 2. Business development strategy by improving the quality of raw materials for spring bed products, developing product designs according to consumer desires, entrepreneurs employing experienced employees in the furniture sector. Providing a guarantee for spring bed products to gain loyalty from consumers. Spring bed buying and selling transactions using a door-to-door system carried out by sales. Spring bed buying and selling transactions via social media Facebook and Tiktok.